Agriculture Resilient at Three Irrigation Modules of Zacatecas, Mexico: Water Scarcity and Climate Variability - Carlos Bautista-Capetillo; Hugo Pineda-Martínez; Luis Alberto Flores-Chaires; Luis Felipe Pineda-Martínez (Agronomy)
Agriculture is the largest consumer of freshwater resources, accounting for approximately 70% of total water withdrawals. In semi-arid regions like Zacatecas, Mexico, water scarcity and climate variability pose critical challenges to small-scale farmers. This study evaluates the effectiveness of integrating modern irrigation technologies with traditional water management practices to enhance agricultural resilience. Analysis of climatic data (1961–2020) revealed a statistically significant increase in annual precipitation of 2.01 mm year−1 in the Leobardo Reynoso module (p < 0.05), while the Miguel Alemán module exhibited a decline ranging from −0.54 mm year−1 to −2.22 mm year−1, exacerbating water scarcity. Pressurized irrigation systems in Leobardo Reynoso improved application efficiency to 87.5%, compared to 50% in traditional furrow irrigation. Despite these advancements, conveyance efficiency remains low (60%) due to extensive open canal networks. Climate projections indicate a 6–11% increase in irrigation water demand for staple crops by 2065, driven by rising evapotranspiration rates. Findings underscore the need for policy interventions, infrastructure upgrades, and financial support to sustain agricultural productivity in water-stressed environments.